Limelight on dark markets: An experimental study of liquidity and information - Aleksander Berentsen; Michael McBride; Guillaume Rocheteau (University of Zurich, Department of Economics, 2013)
The goal of this paper is to study how informational frictions affect asset liquidity in OTC markets in a laboratory setting. The experiments replicate an OTC market similar to the one used in monetary and financial economics (Shi, 1995; Trejos and Wright, 1995; Duffie, Garleanu, and Pedersen, 2005): individuals are matched bilaterally and at random, there are gains from trades due to differences in technologies and endowments, and the terms of trade are determined through a simple bargaining protocol. Subjects buy commodities that have different private values with assets that have common values and can be subject to a private information problem. The asset plays the role of a medium of exchange, but this role can be affected by its lack of recognizability. We study a benchmark experiment where the OTC bargaining game takes place under complete information, a set of experiments with adverse selection where the terminal value of notes are determined exogenously, and a set of experiments with hidden actions where subjects can produce fraudulent notes at some cost.
Keywords: G12; G14; E42; D82; D83; 330; liquidity; money; information; experiments